Motivação e representação cultural no ensino e aprendizagem de inglês como língua estrangeira dos alunos da Licenciatura em Letras da UFPA - VIDAL, Claudia Valéria França (2009)
In the last years cultural issues have gotten more attention in the field of language teaching and learning. Once didactic books are among the main supports in foreign language teaching and learning process, the cultural representations these materials present may influence inlearners beliefs and attitudes in relation to the target language and, consequently, in their motivation to learn it. It is understood that culture encompasses a range of different aspects, however, analyzing the didactic book of English as a foreign language Touchstone, we observed that the cultural samples presented in this material refer basically to historical and geographical aspects and touristic information. We also observed that in relation to the contact with the culture of the target language, the learners of the discipline Anglophone Cultures may have varied attitudes. Thus, this research presents reflections about the considerable limitation of cultural representation in the didactic book analyzed, taking as main focus the extent in which it affects learner’s motivation. Besides, this dissertation presents reflections about how the other’s culture may be approached in order to enhance the perception of his ones’ own culture.